Karakteristik Fisik, Kimia dan Sensoris Kerupuk Keong Mas (Pomacea canaliculata) - Apriyani Apriyani; Indah Widiastuti; Merynda Indriyani Syafutri (Universitas Sriwijaya, 2015)
The objective of this research was to know the physical, chemical and sensory characteristics of snail crackers. The research used factorial randomized block design with difference formulation of snail meat and water as treatments; each treatment was replicated three times. The treatments were the formulation of snail meat (40%, 50%, 60%, 70%, and 80%) and water (60%, 50%, 40%, 30% and 20%). Parameters of research were physical characteristic (fracture, the percentage of expansion, lightness, chroma, and hue), chemical characteristic (water, ash, fat, protein, and carbohydrate by difference content), and sensory characteristic (hedonic test about aroma, colour, fracture and taste). The result showed that the average of fracture ranges from 618.53 gf to 1735.87 gf, the percentage of expansion ranges from 117.67% to 44.17%, lightness ranges from 75.23% to 66.6%, chroma ranges from 9.27% to 13.73%, hue ranges from 89.27o to 79.23o, water content ranges from 2.21% to 2.86%, ash content ranges from 1.39% to 3.03%, fat content ranges from 5.99% to 11.45%, protein content ranges from 3.78% to 7.58%, carbohydrate by difference content ranges from 75.09% to 86.64 % and hedonic test: aroma ranges from 2.8 to 2.84, colour ranges from 2.72 to 3.52, fracture ranges from 2.92 to 3.32 and taste ranges from 2.48 to 3.44. The best treatment of snail crackers was B treatment of formulation of snail meat 50% and water 50%